Facile Synthesis of Coral Reef-Like ZnO/CoS2 Nanostructure on Nickel Foam as an Advanced Electrode Material for High-Performance Supercapacitors - Ikkurthi Kanaka Durga; Kummara Venkata Guru Raghavendra; Naga Bhushanam Kundakarla; Suresh Alapati; Jin-Woo Ahn; Sunkara Srinivasa Rao (Energies, 2021)
Nanocomposite electrodes receive much attention because of their excellent energy storage nature. Electrodes for supercapacitors have come a major source of interest. In this pursuit, the current work elucidates binder-free coral reefs resembling ZnO/CoS2 nanoarchitectures synthesized on the surface of Ni foams employing the cost-effective hydrothermal route. The Zno/CoS2 nanocomposite demonstrated excellent battery-type behavior, which can be employed for supercapcitor application. Various analyses were carried out in the current study, such as X-ray diffraction and high-resolution scanning electron microscopy, which allowed defining the crystalline nature and morphology of surface with ZnO/CoS2 nanoarchitectures. Electrochemical measures such as cyclic voltammetry, galvanostatic charge discharge, and potentiostatic impedance spectroscopy confirmed the battery-type behavior of the material. The synthesized precursors of binder-free ZnO/CoS2 nanostructures depicted an excellent specific capacity of 400.25 C·g−1 at 1 A·g−1, with a predominant cycling capacity of 88. 2% and retention holding of 68% at 10 A·g−1 and 2 A·g−1, even after 4000 cycles, representing an improvement compared to the pristine ZnO and CoS2 electroactive materials. Therefore, the electrochemical and morphological analyses suggest the excellent behavior of the ZnO/CoS2 nanoarchitectures, making them promising for supercapacitors.